The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2106/jbjs.j.00973
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Risk of Recurrence, and Functional Outcome After an Acute Traumatic Posterior Dislocation of the Shoulder

Abstract: The prevalence of posterior dislocation is low. The most common complication after this injury is recurrent instability, which occurs at an early stage in 17.7% of shoulders within the first year after dislocation. The risk is highest in patients who are less than forty years old, sustain the dislocation during a seizure, and have a large humeral head defect. The risk is lower for most patients who sustain the injury from a traumatic accident, especially if they are older and have a small anterior humeral head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
167
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 28 publications
0
167
2
1
Order By: Relevance
“…6,7 To date, all reports mention axial forces applied to the shoulder during anterior elevation, horizontal adduction, and mild inner rotation as the causes of posterior dislocation. 4,8,9 However, the dislocation position of RPDS reported here was completely different from those reported to date. The dislocation occurred when the patient forcibly extended and horizontally abducted his arm with internal rotation, without any direct external force being applied to the shoulder joint.…”
Section: Introductioncontrasting
confidence: 97%
See 1 more Smart Citation
“…6,7 To date, all reports mention axial forces applied to the shoulder during anterior elevation, horizontal adduction, and mild inner rotation as the causes of posterior dislocation. 4,8,9 However, the dislocation position of RPDS reported here was completely different from those reported to date. The dislocation occurred when the patient forcibly extended and horizontally abducted his arm with internal rotation, without any direct external force being applied to the shoulder joint.…”
Section: Introductioncontrasting
confidence: 97%
“…[1][2][3][4][5] Here, we report a case of RPDS associated with the Buford complex. The Buford complex is a normal anatomical variant of the anterosuperior part of the glenoid.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of risk factors for musculoskeletal injuries is an ongoing research initiative across many different organizations. A commonly identified risk factor for future injury is a history of previous injury [10][11][12][13][14][15][16][17]. Injury compromises tissue integrity and impairs functional joint stability [22].…”
Section: Discussionmentioning
confidence: 99%
“…Injury prevention strategies focus on improving human capabilities and reducing modifiable risk factors for injury but the number of prospectively identified risk factors for musculoskeletal injuries remains relatively low. Previous injury is frequently cited and may be the most common prospectively determine risk factor for injury in both civilian and military populations regardless of anatomic location, type of injury, or tissue involved [10][11][12][13][14][15][16][17]. The reasoning is likely multifactorial, and the effect on functional joint stability likely plays a prominent role.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective review of 120 acute, traumatic, isolated posterior GH dislocations Robinson et al [9] found three factors that were significantly associated with an increased risk of recurrent instability: an age <40 years at the time of original dislocation, dislocation during a seizure and the presence of a reverse Hill-Sachs lesion >1.5 cm 3 . Therefore, if a redislocation occurs, an additional adjunctive stabilisation procedure is recommended.…”
Section: Discussionmentioning
confidence: 99%